At the forefront of political psychology essays in honor of John L. Sullivan - Borgida, Eugene; Federico, Christopher M. 1972-; Miller, Joanne M. (Routledge, 2020)
"At the Forefront of Political Psychology pays tribute to John L. Sullivan, one of the most influential political psychologists of his generation. Sullivan's scholarly contributions have deeply shaped our knowledge of belief systems and political tolerance, two flourishing research areas in political psychology that are crucial to understanding the turbulence of our times. This volume, compiled by three of Sullivan's long-time colleagues and collaborators, includes cutting-edge contributions from scholars in political science and psychology. The book is divided into three sections; the first two focus on how Sullivan's work on political tolerance and belief systems influenced generations of political psychologists. The final section offers a more personal look at Sullivan's influence as a mentor to young scholars, many of whom are now intellectual leaders in political psychology. The chapters featured here elucidate how these students were able to flourish under Sullivan's tutelage and life-long mentorship. One of John Sullivan's defining traits is his generosity-as a scholar, mentor, leader, and friend. Over the years, many have benefited greatly from Sullivan's willingness to share his intellect, insight, and passion for democratic values. This impressive collection will appeal to both students and professors of political psychology, but also scholars of social and political behavior, political tolerance, and anyone who has an interest in the contributions made by Sullivan"--
Description based on online resource; title from digital title page (viewed on February 26, 2020)
Keywords: Political psychology; Toleration / Political aspects; Cooperativeness / Political aspects; Public opinion / Political aspects; Ideology